Discrepancy of Academic Performance Between High School and Professional Results of Medical Students - Abida Sultana, Abdul Rehman Shaikh, Abdus Sattar Chaudhry (Journal of Rawalpindi Medical College, 2013)
Background: To determine the difference of academic performance between high school and professional results and their associated factors among medical students . Methods: A cross-sectional descriptive study was carried out among 3rd, 4th and final year students (n=135). Questionnaire contained questions pertaining to socio-demographic profile of the students, boarding status, scores in pre-medical and medical professional exams, consistency of performance, problems encountered in maintaining the performance and reasons for poor performance. Results: Mean score of the students in their pre-medical examination was found to be 84.18%, while 1st and 2nd MBBS professional examination of the students revealed 68.81% and 68.98% result respectively. About 57.8% students were boarders while 42.2% were non-boarders. Of the boarders and non-boarders 42.3% and 73.7% students showed consistent academic performance, respectively. Among boarders 65.4% were troubled by extensive course while about 39% students were apprehensive with evaluation method. Persistent academic performance was registered in 55% and their majority (92%) was constituted by those belonging to upper social class. Majority of the boarders showed performance gap due to stress while the main reason among non-boarders was found to be disinterest in studies. Conclusion: There is gap between high school and professional results. Inadequate performance of medical students was primarily attributed to stress, lower socio-economic status and their disinterest in studies.